Numerical study of heating transfer by natural convection in an inclined elliptical cylinder charged with nanofluid - Amroune, Amina; Bouras, Abdelkrim; Taloub, Djedid; Driss, Zied (Zielona Góra: Uniwersytet Zielonogórski)
In this paper, thermal transfer with natural convection in a tilted annular cylinder with a Cu-water nanofluid has been numerically studied. The hot interior and cold exterior elliptical surfaces of the enclosure were maintained at constant temperatures Th and Tc, respectively. The governing equations were solved by the stream function-vorticity approach. The finite volume approach was utilized to discretise the controlling equations.
Keywords: elliptic cylinder; nanofluid; the Rayleigh number; heat transfer; inclination angle